HIF-2α accumulation in human monocytes upon transfer of hypoxia-associated miRNAs via plasma-derived small extracellular vesicles from head and neck cancer patients - Theodoraki, Marie-Nicole; Hofmann, Linda; Bauer, Helen; Fleckner, Jonas; Depping, Reinhard; Idel, Christian; Plötze-Martin, Kirstin; Penxova, Zuzana; Rades, Dirk; Hoffmann, Thomas K.; Bruchhage, Karl-Ludwig; Pries, Ralph (Frontiers in Oncology, 2026)
Hypoxia is an important hallmark of the tumor microenvironment (TME) in solid tumors and is closely associated with resistance to radiotherapy and a poorer clinical outcome. Tumor-associated plasma-derived small extracellular vesicles (sEVs) have gained increasing attention as an important regulatory TME component for tumor progression and immune evasion. This study aimed to investigate the involvement of plasma-derived sEVs from head and neck squamous cell carcinoma (HNSCC) patients in the systemic regulation of hypoxia-related molecular pathways in circulating immune cells. Plasma-derived sEVs of healthy donors (HDs) and HNSCC patients were isolated and evaluated for morphology, size, miRNA cargo composition, and their influence on monocyte characteristics. Transfer of plasma-derived sEVs from HNSCC patients stimulated increased levels of checkpoint molecule PD-L1 and chemokine CXCL4 secretion. An accumulation of hypoxia-inducible factor (HIF)-2α was associated with hypoxia-regulating miRNAs in sEVs from HNSCC patients. This provides new insights into a proposed tumor-associated systemic sEV-miRNA-mediated hypoxia transfer.